Research Progress toward Room Temperature Sodium Sulfur Batteries: A Review - Yanjie Wang; Yingjie Zhang; Hongyu Cheng; Zhicong Ni; Ying Wang; Guanghui Xia; Xue Li; Xiaoyuan Zeng (Molecules, 2021)
Lithium metal batteries have achieved large-scale application, but still have limitations such as poor safety performance and high cost, and limited lithium resources limit the production of lithium batteries. The construction of these devices is also hampered by limited lithium supplies. Therefore, it is particularly important to find alternative metals for lithium replacement. Sodium has the properties of rich in content, low cost and ability to provide high voltage, which makes it an ideal substitute for lithium. Sulfur-based materials have attributes of high energy density, high theoretical specific capacity and are easily oxidized. They may be used as cathodes matched with sodium anodes to form a sodium-sulfur battery. Traditional sodium-sulfur batteries are used at a temperature of about 300 °C. In order to solve problems associated with flammability, explosiveness and energy loss caused by high-temperature use conditions, most research is now focused on the development of room temperature sodium-sulfur batteries. Regardless of safety performance or energy storage performance, room temperature sodium-sulfur batteries have great potential as next-generation secondary batteries. This article summarizes the working principle and existing problems for room temperature sodium-sulfur battery, and summarizes the methods necessary to solve key scientific problems to improve the comprehensive energy storage performance of sodium-sulfur battery from four aspects: cathode, anode, electrolyte and separator.